A SURVEY OF THE STATUS OF ENVIRONMENTAL HEALTH IN THE RURAL AREAS - B. Samimi; N. Razeghi; A. Mesghali; E. Ghadirian (Tehran University of Medical Sciences, 1972)
In order to have a rational environmental health planning we need to know the status of environmental health and foresee the results of the projects in action. So a general sanitary survey was carried out in 105 villages in Isfahan area in 1969-70. The purposes of this survey were to study the sanitary condition and bacteriblogica1 quality of water in villages with or with out community water supply as well as villages with local water sources (family Wells) and to evaluat6 the effect of the above systems as well as the conditions of latrines and waste disposa1s on the prevalence of enteric infections of bacterial and parasitic natures. The survey showed that 87.6% of villages with community water supplies have water with MNP less than 5 per ml, and 88% of villages with family well waters have water with MNP over 5 per more than the minimum acceptable. In connections with the distribution and prevalence of enteric infections among inhabitants, no differences of statlistica1 significance were observed between different villages enjoying various systems of water or excreta and waste disposal. It seems that many other factors are responsible in the transmission and occurrence of such infections.